2014
DOI: 10.3748/wjg.v20.i37.13521
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor upregulates serotonin transporter and its association with visceral hypersensitivity in irritable bowel syndrome

Abstract: A decrease in EGF levels may contribute to the formation of visceral hypersensitivity through downregulation of SERT-mediated 5-HT uptake into enterocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…4 Indeed, studies showed SERT changes in depression, 35 obsessive-compulsive disorder 36 anxiety, 37 and visceral hypersensitivity. 38,39 Moreover, SERT transgenic mice could reverse key nociceptive signalling and may be a potential approach to treating patients with increased visceral hypersensitivity. 40 In the CAS induced IBS-D rat model, we observed that the level of MPO activity did not differ compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…4 Indeed, studies showed SERT changes in depression, 35 obsessive-compulsive disorder 36 anxiety, 37 and visceral hypersensitivity. 38,39 Moreover, SERT transgenic mice could reverse key nociceptive signalling and may be a potential approach to treating patients with increased visceral hypersensitivity. 40 In the CAS induced IBS-D rat model, we observed that the level of MPO activity did not differ compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGF), an important 53amino acid polypeptide and growth hormone secreted by the salivary glands, liver, pancreas, kidneys, and intestine, 46 upregulates SERT expression in human intestinal tissues through the EGF receptor (R). 47 Cui et al 48 indicated that EGF's upregulating of SERT is associated with visceral hypersensitivity in IBS. One study suggested that p40 prevents cytokine-induced apoptosis in intestinal epithelial cells through an EGFRdependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the S allele results in a lower transcriptional activity of the 5-HTT gene and causes individual differences in sensitivity to daily life stress. This relationship has been observed in both human and animal studies [23]. Stein indicated a high relationship between the presence of the S/S genotype or S allele and a greater susceptibility to affective disorders, and when combined with adverse environmental effects, an increased likelihood of the development of depression was also observed [25].…”
Section: Discussionmentioning
confidence: 82%
“…As described above, the S allele activity was lower than the L allele activity, affecting the concentration of the serotonin transporter, leading to lower transporter expression and therefore lower uptake of 5-HT. Cui et al [23] observed that SERT expression was decreased in colon tissues from visceral-sensitized rats, suggesting a potential association of SERT with the sensitivity of the GI tract. We speculated that the visceral sensitivity may be associated with high UES pressure, but the results of the present study did not show a significant difference in the S/S genotype between the subgroups.…”
Section: Discussionmentioning
confidence: 99%